Single-Cell Analysis of SMN Reveals Its Broader Role in Neuromuscular Disease - Natalia Rodriguez-Muela; Nadia K. Litterman; Erika M. Norabuena; Jesse L. Mull; Maria José Galazo; Chicheng Sun; Shi-Yan Ng; Nina R. Makhortova; Andrew White; Maureen M. Lynes; Wendy K. Chung; Lance S. Davidow; et al. (Cell Reports, 2017)
The mechanism underlying selective motor neuron (MN) death remains an essential question in the MN disease field. The MN disease spinal muscular atrophy (SMA) is attributable to reduced levels of the ubiquitous protein SMN. Here, we report that SMN levels are widely variable in MNs within a single genetic background and that this heterogeneity is seen not only in SMA MNs but also in MNs derived from controls and amyotrophic lateral sclerosis (ALS) patients. Furthermore, cells with low SMN are more susceptible to cell death. These findings raise the important clinical implication that some SMN-elevating therapeutics might be effective in MN diseases besides SMA. Supporting this, we found that increasing SMN across all MN populations using an Nedd8-activating enzyme inhibitor promotes survival in both SMA and ALS-derived MNs. Altogether, our work demonstrates that examination of human neurons at the single-cell level can reveal alternative strategies to be explored in the treatment of degenerative diseases.